Future of Renewable Energy Use in Pakistan in the Context of Agrifood-Energy Nexus - Bhandari, Ramchandra; Kumar, Bhunesh (Journal of the Institute of Engineering, 2020)
Pakistan is facing a serious energy supply problem due to lack of energy that results in a shortfall of power supply from 6–10 hours/day, especially outside the big cities. The energy demand is expected to increase in every sector such as industrial, agricultural, household and transport in the years ahead due to population growth, economic development and modern lifestyle. Agricultural sector plays a vital role in the country’s economy contributing around 20% share in GDP. At present the direct energy consumption in the agricultural sector is 2%. To avoid a worse situation in the future years renewable energy resource potential exploitation is needed. This requires also proper planning and implementation of energy policies. In this work present and future electrical energy consumption, demand and supply gap of the country is presented. A sustainable agricultural productive system has become a major priority to maintain food security for the increasing population. Both direct and indirect electrical and energy consumption has emerged in agrifood sector with farm machinery, production, packing and transport of fertilizers, food processing and transport, crop production, animal product production, poultry production, etc. In addition to this excel based model is developed to integrate the renewable energy into the agrifood – energy nexus supply chain and to fulfil the current and future energy demand of the sector.